Estudio de prefactibilidad para la instalación de una planta productora de café Mishasho - Herrera Rios, Diego Raul (2020)
This study has demonstrated the feasibility of market, technological, economic, financial and social to install a production plant of Café Mishasho destined to the city of Lima. The project considers an investment of S / 767.494 and has the following economic indicators: NPV (Net Present Value) of S / 340.226, IRR (Internal Rate of Return) of 37,26% and a recovery period of 3 years 7 months and 17 days. One of the main strengths of the project is that the product will be new in the Lima market and according to the analysis of demand made by being innovative and having arrival through all the most used sales channels in the country, a constant growth is expected by minimum a 10 years period. Regarding the product itself, it will be presented ground and packed in bags of 100 gr, respecting DIGESA quality standards, national and international technical standards. A project demand for the year 2023 of 15.118,00 bags of 100gr has been estimated. The facilities will be located in the city of Chanchamayo in the province of Junín mainly due to the availability of raw materials and proximity to the target market. The plant size for the project is defined by market size and is 15,118.00 bags of coffee. Also, the plant capacity is 37,630 bags determined by the packaging operation because it is the bottleneck. The production program for the 5-year life of the project is 900 bags per day, using a plant installed in an area of 925 m². The project also has positive financial indicators that reinforce the viability of the project.